2014
DOI: 10.1002/ejic.201402156
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Hybrid Porous Materials from Cubic Octavinylsilsesquioxane through Friedel–Crafts Reaction Using Tetraphenylsilane as a Concentrative Crosslinker

Abstract: A series of novel hybrid porous polymers (HPPs), derived from cubic octavinylsilsesquioxane (OVS; [(C2H3SiO1.5)8]) and tetraphenylsilane (TPS), were successfully synthesized through Friedel–Crafts alkylation reaction. The porosities of the HPPs could be tuned by modulating the molar ratio of OVS and TPS. The HPPs showed high porosity, with Brunauer–Emmett–Teller specific surface areas of 518–989 m2 g–1, and total pore volumes of 0.35–0.76 cm3 g–1, as well as narrow pore‐size distributions. For gas sorption app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 41 publications
3
55
0
Order By: Relevance
“…HP-TPPs and HP-TPPOs, respectively, as shown in Scheme 3. 30,32,33 The symmetric stretching vibrations of P]O at 1187 cm À1 (Fig. These hybrid porous polymers were rst characterized by FTIR spectroscopy.…”
Section: Synthesis and Characterization Of Hybrid Porous Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…HP-TPPs and HP-TPPOs, respectively, as shown in Scheme 3. 30,32,33 The symmetric stretching vibrations of P]O at 1187 cm À1 (Fig. These hybrid porous polymers were rst characterized by FTIR spectroscopy.…”
Section: Synthesis and Characterization Of Hybrid Porous Polymersmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Recently, many hybrid porous polymers were prepared via the topology combination from cubic OVS with planar molecules, 30 tetrahedral molecules, 31,32 cubic molecules [33][34][35][36] and polymer. [22][23][24][25][26][27][28][29] Recently, many hybrid porous polymers were prepared via the topology combination from cubic OVS with planar molecules, 30 tetrahedral molecules, 31,32 cubic molecules [33][34][35][36] and polymer.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous reports, traditional hypercrosslinking porous polystyrenes were prepared by the precursor of linear polystyrene through adding small molecule of divinyl benzene as a crosslinking agent via the Friedel-Cras alkylation reaction. 39 The rigid cage makes it a potential nanobuilding block to form porous materials via the stacking of POSS cages. The polymeric chains extended through the whole initial solution (or gel) and remained strongly solvated over all period of network formation.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25] As a silica-like cage compound, polyhedral oligomeric silsesquioxane (POSS) provides an excellent platform for synthesis of new inorganicorganic hybrid materials with enhanced thermal and mechanical properties. 38,39 It was observed that S BET increased with the increasing reactive sites of benzene, i.e. These hybrid polystyrene based on POSS exhibited the improved thermal stabilities, 27,28 viscoelastic properties, 29,30 magnetic properties 31 compared to the pristine polystyrene.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation